Measuring Preferences Over Intertemporal Profiles - Chen Sun (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Growing evidence indicates that utility over time is different from utility under risk. Hence, measuring intertemporal preferences (discounting and utility) exclusively from intertemporal choices is desirable. We develop a simple method for measuring intertemporal preferences. It is parameter-free in both discounting and utility, and allows a wider range of models to be measured than preceding methods. It is easy to implement, clear to subjects, incentive compatible, and does not require more measurements than existing methods if identical assumptions are imposed. In an experiment, we illustrate how the method can be used to test recent models with unconventional assumptions non-parametrically.
Keywords: C91; D12; D91; 330; measuring time preferences; intertemporal profile; parameter-free